A survey of Lolium rigidum populations in citrus orchards: Factors explaining infestation levels. Issue 3 (7th July 2015) - Atanackovic, Valentina; Juárez‐Escario, Alejandro; Recasens, Jordi; Torra, Joel
<x xml:space="preserve">Abstract</x> The presence of herbicide‐resistant Lolium rigidum in Mediterranean (Spanish) citrus orchards was reported in 2005 and it poses a serious threat to crop management. The main objective of this research was to investigate which components could be responsible for the persistence of annual ryegrass populations in Mediterranean mandarin and orange orchards. This is the first study regarding L. rigidum populations in Mediterranean citrus orchards. Surveys were conducted in 55 commercial citrus orchards in eastern Spain in 2013 by interviewing technicians who were working in cooperatives about crop management. The level of infestation by L. rigidum and the presence of harvester ants (Messor barbarus) then were estimated in the same orchards. The variables were subjected to a two‐dimensional analysis and both univariate and multivariate logistic regression models were fitted for each of the three L. rigidum density levels that had been established. The multivariate models showed the significant factors that were associated with various L. rigidum densities: (i) at a low density, the herbicides that were applied, the number of applications in 2013 and the type of irrigation (flood or drip); (ii) at a medium density, the presence of harvester ants; and (iii) at a high density, the herbicides that were applied in 2013. The results indicated that drip irrigation and one application of glyphosate mixed with other herbicides (or herbicides other than glyphosate) were associated with a lower L. rigidum density. The alternative management options that are presented here should help farmers to reduce weed problems in Mediterranean citrus orchards. Future research is required to better understand the presence of herbicide‐resistant populations, as well as the possible beneficial presence of granivorous ant species.